A Study on a Currency peg in the GCC Region with a Special Focus on UAE and its Impact on Economic Development - El Alami, Ala (2013)
When there is trading operations which involves exports and imports for a country then currency is required for the purpose of exchange of goods and services. The currency in which two countries exchange goods and services are fixed so they can select the currency in which one of the countries trades in commonly, or choose a currency of even a third country to deal in. Some countries peg their currency to avoid any confusion in future. In this research report, the aspect of currency agreement which is adopted in UAE and other GCC countries for the purpose of trading is studied. The aim of this report is to examine and evaluate the advantages and disadvantages of fixing the currency. The report also provides information on what determines the correlation by pegging the currency with US dollar, euro and independent float and the best way to establish which way should be adopted for the trading of goods and services. In the literature review the various aspects associated with currency such as common currency, currency board, GCC currency union and pegging to dollar and global currency system has been mentioned in brief details. There are two methods in this report – primary method and secondary method. In the primary method data has been collected related to the values of `different currencies from 2004 till 2011 and with the help of statistical tools, correlation of UAE dirham is found out with the different currencies. Also correlation between economic indicators and currency fluctuation has been determined. In the secondary method literature review of articles, scholarly journals, newspapers, magazines, and internet websites related to the topic is referenced.